Medico-legal Closed Case Trends in Canadian Plastic Surgery: A Retrospective Descriptive Study. Issue 8 (August 2021) - Zhang, Zach; Calder, Lisa; Finestone, P.J.; Liu, Richard; Bucevska, Marija; Arneja, Jugpal S.
Abstract : Background: To enhance patient safety and prevent medico-legal complaints, we need to understand current trends and impacts. We aimed to characterize Canadian plastic surgery medico-legal patterns in many dimensions. Method: This retrospective descriptive analysis of Canadian Medical Protective Association data between January 1, 2013 and December 31, 2017 included closed regulatory body complaints and civil-legal actions involving plastic surgeons. We excluded class action legal cases and hospital complaints. We collected data on patient allegations, procedure types, healthcare-related patient harms, and peer expert criticisms. The primary outcome of interest was physician medico-legal outcome. Results: We found 414 cases that met the inclusion criteria: 253 (61.1%) cases involved cosmetic procedures and 161 (38.9%) noncosmetic procedures. The annual incidence among plastic surgeon members of regulatory body complaints and civil-legal actions was 12.1% and 6.7%, for a combined incidence of 18.8%. The most common allegations were deficient clinical assessment, inadequate informed consent, delayed or misdiagnosis, and inadequate monitoring. Leading contributing factors were physician–patient communication breakdown, deficient clinical judgments, and inadequate documentation. The top procedural complications included cosmetic deformity, poor scarring, upper extremity stiffness or deficit, major structural injury, and mental health disorder. Less than half of cases (198/414, 47.8%) had unfavorable medico-legal outcomes for the surgeon. Patients were compensated in 86/198 (43.4%) of civil-legal cases. Conclusions: Plastic surgeons experience more medico-legal complaints for cosmetic versus noncosmetic procedures. To minimize medico-legal risks, plastic surgeons should focus on strong physician–patient communication, patient education/consent, thorough clinical assessment, minimizing potentially preventable complications, and maintaining relevant documentation.